Deformation monitoring of Surakachhar underground coal mines of Korba, India using SAR interferometry. Issue 12 (15th December 2022) - Monika,; Govil, H.; Chatterjee, R.S.; Bhaumik, Pralay; Vishwakarma, Neeraj
Abstract: Underground mines around the globe experience the deformation/subsidence due to the wornd practiced of the mining activity or by the geological failure. In this study deformation monitoring of Korba underground coal mines in Chhattisgarh, India was performed using the Synthetic aperture radar remote sensing. In this study, the Surakachhar 5/6 underground coal mining region of Korba area and its surrounding are considered for deformation/displacement monitoring. The displacement estimation was generated using Advanced Differential Interferometric Synthetic Aperture Radar (ADInSAR) technique: Persistent Scatterer SAR interferometry (PSInSAR) and Ground-based investigation for validation and impact assessment have also been performed. PSInSAR results, obtained by processing of 17 Sentinel-1A images (Feb-2015 to Feb-2017) showed that multiple areas above the underground mining have been deformed around 3 mm/year to −21 mm/year along the radar line of prospect. Deformed regions are mainly on the surface of active mining areas and settlements. Deformation mapping using PSInSAR with ground-based investigation provides an account learning of Surakachhar underground mining activities, consequences such as sag, pit and cracks in the area. This technique helps to predict the hazard-prone deformation/subsidence zone and to prevent serious damage due to roof failure in the near future.